This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Hello, like what the title said, do not be fooled into thinking that you can factorise the left hand side of the equation to a^2+2ab+b^2.
7x+7+2(49x^2+7x-42)^(1/2) + 7x-6 = 182 - (7x+7)^(1/2) - (7x-6)^(1/2)
Then ((7x+7)^(1/2) + (7x-6)^(1/2))^2 = 182 - (7x+7)^(1/2) - (7x-6)^(1/2)
Let a = (7x+7)^(1/2) + (7x-6)^(1/2) so that a^2 = 182 - a. Solving we get a=-14 or 13 but we reject the negative solution as square roots are always positive.
Solving for x we get x=6.